El accidente cerebrovascular desde la mirada del rehabilitador - Moyano V., Álvaro (Revista Hospital Clínico Universidad de Chile, 2010)
Stroke is the most common acquired neurological disease in the adult population worldwide. With advances in medicine, mortality from this cause has declined significantly, generating greater number of disabled as a result. Rehabilitation in stroke patients should be started early even in complex care units and follow-up extended beyond the recovery phase; should constitute a continuum of actions in time seeking to minimize the neurological deficit and its complications, encourage family and social reintegration of the individual and improve their quality of life. For this, the rehabilitation team must use all the techniques and technology that have proved useful in managing these patients in different stages of rehabilitation.